Use of Complementary and Alternative Medicine Among Patients With Epilepsy and Diabetes Mellitus, Focusing on the Outcome of Treatment - Girgis, Michael Magdy Fahmy; Fekete, Klára; Homoródi, Nóra; Márton, Sándor; Fekete, István; Horváth, László (Frontiers in Neuroscience, 2022)
Introduction Millions all over the world live with epilepsy and they may require long-term drug treatment. The use and interest in complementary and alternative medicine (CAM) have grown over the previous years. Co-administration of herbal products with medicines may result in adverse drug reactions (ADR) and/or unfavourable interactions. The aims of this study were to determine the prevalence of CAM use among patients with epilepsy and, also, to compare the results to those of the patients with diabetes mellitus (DM); to reveal factors that may drive the use of CAM; and to measure outcomes and adherence. It was also our intent to have state-of-art information of CAM use in our region among patients with the two diseases above. Methods We conducted a non-interventional study using a self-developed questionnaire. It was distributed among adult patients with either epilepsy or diabetes mellitus who also suffered from cardiovascular consequences. A database was compiled from the anonymous questionnaires, filled in voluntarily by the patients. Basic statistics were used to analyse this database. Results A total of 227 questionnaires were filled in by 127 patients (55.9%) with epilepsy and 100 patients (44.1%) with diabetes mellitus. Mean age was 54.54±17.33 years. Of the patients, 50.2% were male. Average body weight was 80.3±17.3 kg. Of the patients, 22 (9.7%) used CAM because they believed in CAM. Two of them reported ADR. Among the patients with epilepsy, the ratio was only 7.9% compared to 12% among those with diabetes mellitus. While the number of CAM users was higher among younger patients with epilepsy, it was the elderly patients with diabetes mellitus who tended to use CAM. Conclusion Attention should be paid to reliance on CAM during the follow-up. Our finding that health-conscious patients tend to use CAM more often (than the general population) may indicate it is necessary to discuss CAM usage sincerely. CAMs modulating CYPs enzymes were the most common, leading to interactions with medication used and resulting in ADR. This shows the importance of educating patients and treating team including clinical pharmacist in this field is essential.